Time to resolution and effect on quality of life of molluscum contagiosum in children in the UK: a prospective community cohort study - Olsen, JR; Gallacher, J; Finlay, AY; Piguet, V; Francis, NA (Elsevier, 2014)
Background Molluscum contagiosum is one of the 50 most prevalent diseases worldwide, but scarce epidemiological data exist for childhood molluscum contagiosum. We aimed to describe the time to resolution, transmission to household child contacts, and effect on quality of life of molluscum contagiosum in children in the UK.